Surgical care practitioners: an audit across the surgical specialties. (9th June 2022) - Fletcher, Nicholas; Russell, Bradley
Abstract : Introduction: The Royal College of Surgeons of England (RCS), when devising their curriculum for surgical care practitioners (SCPs), aimed to provide a level of training to produce a practitioner able to work across the surgical patient's journey, providing care to, arguably, an advanced level. This audit planned to examine the reality of this. Method: SCPs from a closed group, on the Facebook social media platform were invited to complete an online questionnaire about their role as an SCP. Results: A total of 92 responses were gathered from across the surgical specialty SCP community and from around the UK. Data were collected on the breakdown of the SCP's role and working practices. Conclusion: The data collected demonstrated the multifunctional nature of the SCP and their ability to work at a level as envisioned by the RCS curriculum.